Advances in information optics and photonics - Friberg, Ari T., 1951-; Dändliker, R. (SPIE monograph ;, 2008)
In this age of the photon, information optics and photonics represent the key technologies to sustain our knowledge-based society. New concepts in classical and quantum-entangled light, coherent interaction with matter, and novel materials and processes have led to remarkable advances in today's information science and technology. The ICO is closely involved with information optics, as exemplified by the ICO topical meeting on Optoinformatics / Information Photonics (St. Petersburg, Russia, 2006), the ICO/ICTP Winter College on Quantum and Classical Aspects of Information Optics (Trieste, Italy, 2006), and the many ICO Prizes recently awarded on outstanding contributions on these topics. This book is in part based on these ICO activities.